Blockade of the High-Affinity Interleukin-2 Receptors with Daclizumab High-Yield Process: Pharmacokinetic/Pharmacodynamic Analysis of Single- and Multiple-Dose Phase I Trials - Minocha, Mukul; Tran, Jonathan Q.; Sheridan, James P.; Othman, Ahmed A. (Clinical pharmacokinetics, 2016)
Background and Objective Daclizumab high-yield process (DAC HYP) is a humanized monoclonal antibody that selectively blocks the α-subunit (CD25) of the high-affinity interleukin-2 receptors, and has shown robust efficacy as a treatment for multiple sclerosis (MS). This work quantitatively characterized the relationship between DAC HYP serum concentrations and saturation of CD25 expressed on antigen-rich target T cells in blood. Methods Serial pharmacokinetic and 968 CD25 measurements from three double-blind, randomized, placebo-controlled, phase I studies of DAC HYP (50–300 mg subcutaneous and 200–400 mg intravenous doses or placebo) in healthy volunteers ( n